Learning from the QUEST multicentre feasibility randomization trials in breast reconstruction after mastectomy. Issue 1 (January 2015) - Winters, Z. E.; Emson, M.; Griffin, C.; Mills, J.; Hopwood, P.; Bidad, N.; MacDonald, L.; Turton, E. P. L.; Horne, R.; Bliss, J. M.; the QUEST Trial Management Group; Barr, L.; et al.
<x xml:space="preserve">Abstract</x> Background Breast reconstruction aims to improve health‐related quality of life after mastectomy. However, evidence guiding patients and surgeons in shared decision‐making concerning the optimal type or timing of surgery is lacking. Methods QUEST comprised two parallel feasibility phase III randomized multicentre trials to assess the impact of the type and timing of latissimus dorsi breast reconstruction on health‐related quality of life when postmastectomy radiotherapy is unlikely (QUEST A) or highly probable (QUEST B). The primary endpoint for the feasibility phase was the proportion of women who accepted randomization, and it would be considered feasible if patient acceptability rates exceeded 25 per cent of women approached. A companion QUEST Perspectives Study (QPS) of patients (both accepting and declining trial participation) and healthcare professionals assessed trial acceptability. Results The QUEST trials opened in 15 UK centres. After 18 months of recruitment, 17 patients were randomized to QUEST A and eight to QUEST B, with overall acceptance rates of 19 per cent (17 of 88) and 22 per cent (8 of 36) respectively. The QPS recruited 56 patients and 51 healthcare professionals. Patient preference was the predominant reason for declining trial entry, given by 47 (53 per cent) of the 88 patients approached for QUEST A and 22 (61 per cent) of the 36 approached for QUEST B. Both trials closed to recruitment in December 2012, acknowledging the challenges of achieving satisfactory patient accrual. Conclusion Despite extensive efforts to overcome recruitment barriers, it was not feasible to reach timely recruitment targets within a feasibility study. Patient preferences for breast reconstruction types and timings were common, rendering patients unwilling to enter the trial.